Analysis of Graduates’ Soft Skills of Vocational High School Majoring in Software Engineering Skill Competence in Startup Industry - Ayuningtyas Kurniawati; Didik Nurhadi; Syaad Patmanthara (Universitas Ngeri Malang, 2023)
Facing the 4.0 industrial revolution, the graduates of Vocational High School (SMK) majoring in Software Engineering need to equip themselves to elevate their competence. Hard skills should be balanced with soft skills to compete globally, particularly in the startup industry. Facts revealed that the vocational high school graduates majoring in software engineering had not met the expectations of the startup industry, which put a more substantial concern on soft skills. This study aimed to reveal the soft skills required by the startups that vocational high school graduates majoring in software engineering need to acquire. The result of this study showed that the need for soft skills among vocational high school graduates majoring in software engineering who worked in the startup industry still needed to be improved, covering several aspects in the following: (1) critical thinking and problem-solving skills; (2) active communication skill both spoken and written; and (3) emotional quotient. It can be implied from the result that attempts are needed to increase the soft skills of vocational high school graduates majoring in software engineering to compete globally and fulfill the needs of the startup industry. The attempts should be a substantial concern among the policy maker as an institution determining the national curriculum to support the skill improvement of hard and soft skills. On the other hand, the stakeholders of Vocational High Schools need to advance the collaboration with the industrial world to equip the graduate candidates majoring in software engineering to quickly meet the needs of the labor market in the startup industry. Menghadapi revolusi industri 4.0, lulusan Sekolah Menengah Kejuruan (SMK) jurusan Rekayasa Perangkat Lunak perlu membekali diri untuk meningkatkan kompetensinya. Hard skill harus diimbangi dengan soft skill untuk bersaing secara global, khususnya di industri startup. Fakta menunjukkan bahwa lulusan SMK jurusan rekayasa perangkat lunak belum memenuhi ekspektasi industri startup yang lebih mementingkan soft skill. Penelitian ini bertujuan untuk mengungkap soft skill yang dibutuhkan oleh startup yang perlu dimiliki oleh lulusan sekolah menengah kejuruan jurusan rekayasa perangkat lunak. Hasil penelitian menunjukkan bahwa kebutuhan soft skill pada lulusan SMK jurusan rekayasa perangkat lunak yang bekerja di industri startup masih perlu ditingkatkan, meliputi beberapa aspek sebagai berikut: (1) kemampuan berpikir kritis dan pemecahan masalah; (2) keterampilan komunikasi aktif baik lisan maupun tulisan; dan (3) kecerdasan emosional. Dari hasil tersebut dapat tersirat bahwa diperlukan upaya untuk meningkatkan soft skill lulusan SMK jurusan rekayasa perangkat lunak agar dapat bersaing secara global dan memenuhi kebutuhan industri startup. Upaya tersebut patut menjadi perhatian besar di kalangan pengambil kebijakan sebagai lembaga penentu kurikulum nasional untuk mendukung peningkatan keterampilan hard skill dan soft skill. Di sisi lain, pemangku kepentingan SMK perlu memajukan kerjasama dengan dunia industri untuk membekali calon lulusan jurusan rekayasa perangkat lunak agar dapat segera memenuhi kebutuhan pasar kerja di industri startup.